UNCOVERING THE WEIGHTINESS OF GREEN MARKETING MIX AND CONSUMER ATTITUDE IN COSMETIC PRODUCT - Putri, Denysa Karisma; Anjaningrum, Widiya Dewi (LP2M Institut Teknologi dan Bisnis Asia Malang, 2022)
This study aims to determine the impact of the green marketing mix and consumer attitudes towards brand image and purchasing decisions, as well as to determine the mediating function of brand image. The object of this research is consumers of Love Beauty and Planet in Malang town with a total sample of 190 respondents who were selected by non-probability sampling technique. Quantitative data collected through questionnaires were analyzed using Partial Least Square (PLS) analysis. The results of the study reveal that the green marketing mix and consumer attitudes have a positive and strong direct impact on brand image and purchasing decisions, which brand image is also proven to be a mediator. It is recommended for further research to reveal more in-depth which dimension of green marketing is suitable to be seeded to make the brand image of Love Beauty and Planet getting stronger and the purchasing decisions of its customer increasing rapidly.